Post-inflammatory pulmonary fibrosis in a discharged COVID-19 patient: Effectively treated with Pirfenidone - Zhan Xi; Zhao Zhigang; Li Ting (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
The coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) has led to a pandemic situation. According to the WHO classification, COVID-19 patients could be classified with severity as uncomplicated illness, mild pneumonia, severe pneumonia, acute respiratory distress syndrome (ARDS), sepsis, and septic shock [1]. China has controlled the situation and thousands of patients had been discharged. We noticed that most patients of severe pneumonia or ARDS had post-inflammatory pulmonary fibrosis (PPF) during follow-up after the cure of COVID-19. Here we report a case of PPF resulting from COVID-19 effectively treated with Pirfenidone, an antifibrosis medication.